Design and Development of Cages for the Next Generation Self-Aligning Bearings - Kuhalampi, David; Sadeghi, Niki (My University, 2023)
Roller bearings can provide a self-aligning quality when the rollers have a toroidal shape. The bearing can also take up both axial and radial forces when the rollers are inclined. By implementing a new bearing cage with lower cost and an excellent dynamic function, the SAT-bearing by SKF could become a strong competitor and the primary alternative for turbine shafts in wind power applications. By investigating polymer as a material for the bearing cage, factors such as design freedom, carbon footprint and price could be optimised. The scope was limited to the wind power application for a reference for application-specific parameters such as service temperature, rpm and lifespan. During this project, a traditional product development approach was used to design and develop concepts for new bearing cages for the SAT bearing. The information retrieval consisted of interviews with experts on the topic, as well as studying internal and external literature and resources. Three unique concepts were generated and screened using traditional product development methods and were tested and simulated before being developed further. During this process, a selection of polymer materials was also studied and compared. The cage designs were driven by their CAD models which were continuously improved throughout the process. It was proved that using a polymer material instead of steel could o
Keywords: bearing cage, polymer cage, roller bearing, self-aligning bearing